Применение емкостного разряда для накачки CuBr-лазеров; Лазеры и лазерные технологии - Губарев Ф. А. Фёдор Александрович; Шиянов Д. В. Дмитрий Валерьевич; Суханов В. Б. Виктор Борисович; Тригуб М. В. Максим Викторович (2010, 2010)
В фонде НТБ ТПУ отсутствует